Immanent Visitor : Selected Poems of Jaime Saenz - Sáenz, Jaime (Book collections on Project MUSE., 2002)
Immanent Visitor is the first English-language translation of the work of Bolivia's greatest and most visionary twentieth-century poet. A poete maudit, Jaime Saenz rejected the conventions of polite society and became a monk in service of his own imagination.